2021
DOI: 10.1371/journal.pone.0257538
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine tidal range dynamics under rising sea levels

Abstract: How an estuary responds to sea level rise (SLR) is complex and depends on energy drivers (e.g., tides and river inflows), estuarine geometry (e.g., length and depth), intrinsic fluid properties (e.g., density), and bed/bank roughness. While changes to the tidal range under SLR can impact estuarine sediment transport, water quality, and vegetation communities, studies on the altered tidal range under SLR are often based on case studies with outcomes applicable to a specific site. As such, this study produced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 97 publications
(129 reference statements)
1
13
0
Order By: Relevance
“…High risk drainage areas (those with short drainage windows) are associated with tidal dampening or positive water level asymmetry. Tidal dampening is commonly associated with longer estuaries, estuaries which are prismatic or weakly converging, or those with restricted entrances (Khojasteh, Chen, et al., 2021). Areas with extensive intertidal flats are also susceptible to tidal dampening (Du et al., 2018; Lee et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High risk drainage areas (those with short drainage windows) are associated with tidal dampening or positive water level asymmetry. Tidal dampening is commonly associated with longer estuaries, estuaries which are prismatic or weakly converging, or those with restricted entrances (Khojasteh, Chen, et al., 2021). Areas with extensive intertidal flats are also susceptible to tidal dampening (Du et al., 2018; Lee et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dampening of the tidal range is typically experienced where the effects of friction dominate the tidal wave energy or there is an expansion in the area of flow, for example, where low‐lying land is inundated or channel banks diverge (Khojasteh, Glamore, et al., 2021; Talke & Jay, 2020). Conversely, tides may be amplified by a gradual contraction in the width or depth of an estuary (respectively termed funneling and shoaling) or by reflection or resonance of the tidal wave (Khojasteh, Glamore, et al., 2021; Talke & Jay, 2020). The net effect on estuarine water levels will depend on the relative impact of each of these influences (Friedrichs, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of SLR on tidal dynamics are complex as they result from nonlinear interactions among forcing drivers, estuarine morphology, fluid properties, and friction factors. A comprehensive modeling approach of estuarine tidal response to both rising sea levels and RF scenarios showed that tides are either attenuated in short estuaries characterized by low tidal ranges or amplified in prismatic and converging estuary types (Khojasteh et al, 2021a;Khojasteh et al, 2021b). Specifically, our results suggest that SLR will increase tidal range along the navigational channel (e.g., 9.9 cm for M-M scenario and under RCP 4.5 and 8.5, respectively) and agree well with similar studies conducted in the Gulf of Mexico (e.g., an increase up to 10.0 cm under the 2100-high scenario (Passeri et al, 2016)).…”
Section: U Wd D Wse Bl Dmentioning
confidence: 99%
“…Next to the physical effects of channel dredging, sea level rise (SLR) amplifies tidal range in convergent estuaries and estuarine systems characterized by strong RFs (Khojasteh et al, 2021a). SLR modifies wetland spatial distribution and tidal hydrodynamics over time, which in turn alters wetland inundation dynamics (Alizad et al, 2016;Kumbier et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These include reasonably simple indicator techniques (Rogers and Woodroffe 2016) and simple bath-tub modelling. Alternatively, more sophisticated approaches could be used, such as projections of tidal planes (Hanslow et al 2018), geomorphological modelling (Rogers et al 2014;Mogensen and Rogers 2018), or hydrodynamic modelling (Rodríguez et al 2017;Kumbier et al 2018;Khojasteh et al 2021). Integration with tidal plane analyses (Wen and Hughes 2022) may increase confidence in possible future retreat pathways and can be used to identify retreat pathways where decisions can be made now to improve blue carbon futures.…”
Section: Recommendations For Blue Carbon Opportunities In Nswmentioning
confidence: 99%